Data and optimisation requirements for Kidney Exchange Programs. (April 2021) - Smeulders, Bart; Pettersson, William; Viana, Ana; Andersson, Tommy; Bolotinha, Catarina; Chromy, Pavel; Gentile, Margherita; Hadaya, Karine; Hemke, Aline; Klimentova, Xenia; Kuypers, Dirk; Manlove, David; et al.
Kidney Exchange Programs (KEP) are valuable tools to increase the options of living donor kidney transplantation for patients with end-stage kidney disease with an immunologically incompatible live donor. Maximising the benefits of a KEP requires an information system to manage data and to optimise transplants. The data input specifications of the systems that relate to key information on blood group and Human Leukocyte Antigen (HLA) types and HLA antibodies are crucial in order to maximise the number of identified matched pairs while minimising the risk of match failures due to unanticipated positive crossmatches. Based on a survey of eight national and one transnational kidney exchange program, we discuss data requirements for running a KEP. We note large variations in the data recorded by different KEPs, reflecting varying medical practices. Furthermore, we describe how the information system supports decision making throughout these kidney exchange programs.